2010
DOI: 10.1099/mic.0.032623-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of DNA repeats in Burkholderia cenocepacia J2315 identifies a novel adhesin-like gene unique to epidemic-associated strains of the ET-12 lineage

Abstract: Members of the Burkholderia cepacia complex (Bcc) are respiratory pathogens in patients with cystic fibrosis (CF). Close repetitive DNA sequences often associate with surface antigens to promote genetic variability in pathogenic bacteria. The genome of Burkholderia cenocepacia J2315, a CF isolate belonging to the epidemic lineage Edinburgh-Toronto (ET-12), was analysed for the presence of close repetitive DNA sequences. Among the 422 DNA close repeats, 45 genes potentially involved in virulence were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 50 publications
(46 reference statements)
1
55
0
Order By: Relevance
“…In a previous study, we reported that the BCAM0224 gene was detected exclusively in epidemic B. cenocepacia strain J2315. We also found that a B. cenocepacia BCAM0224 mutant exhibited attenuated virulence in a Galleria mellonella infection model (22).…”
mentioning
confidence: 57%
See 4 more Smart Citations
“…In a previous study, we reported that the BCAM0224 gene was detected exclusively in epidemic B. cenocepacia strain J2315. We also found that a B. cenocepacia BCAM0224 mutant exhibited attenuated virulence in a Galleria mellonella infection model (22).…”
mentioning
confidence: 57%
“…In a previous work (22), we identified the BCAM0224 gene, encoding a protein with similarity to the prototype member of the TAA family, the Yersinia adhesin YadA. In an attempt to gain insight into its structure, we have built 3D models for BCAM0224 domains using the Webbased I-TASSER server (http://zhanglab.ccmb.med.umich.edu /I-TASSER/) (26).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations